DETERMINASI STRUKTUR MODAL PERUSAHAAN DI BIDANG MANUFAKTUR YANG TERDAFTAR PADA INDEKS LQ 45 BURSA EFEK INDONESIA PERIODE 2010-2014 - Rizki Juniarti (Operations Excellence: Journal of Applied Industrial Engineering, 2014)
Abstract. The purpose of this study is to analyze the determination factors ofcapital structure, such as deficit, profitability and tangibility asset, and theirinfluence to the use of short term debt, long term debt and total debt, based on twoperspective namely Pecking Order Theory (POT) and Trade-off Theory (TOT).From the perspective of POT, company has a certain order to choose theirfinancing decision. The order start from internal to external financing. Thus, inPOT, deficit has positive influence to the debts while profitability and tangibilityasset have negative influences. From the perspective of TOT, debts are able toprovide advantage to offset the tax value. Thus, based on TOT, deficit,profitability and tangibility asset have positive influence to the debts. The samplesof this study are 10 manufacturing companies listed in LQ45 for minimum of fourperiods in 2010-2014 with OLS Regression as the analysis method. The resultsimplied that in terms to the use of short term debt and total debt, financingdecision of sample companies has no path suggested by POT nor TOT; however,regarding the uses of long term debt, the companies follows the path suggested byPecking Order Theory.Keywords: Deficit, Profitability, Tangibility Asset, Debts, Pecking Order Theory,Trade-off Theory